2009
DOI: 10.1103/physrevlett.103.257202
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Charge States of Molecules with Spin-Flip Spectroscopy

Abstract: The charge states of single molecular magnetic chains were manipulated with a scanning tunneling microscope and identified by spin-flip inelastic tunneling spectroscopy. We show that the charged and neutral states have different spin structures and therefore exhibit different features associated with the spin-flip processes in tunneling spectra. The experiment demonstrates a general approach for detecting the charge states at the nanometer scale in a more straightforward manner than using indirect information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
217
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(238 citation statements)
references
References 27 publications
19
217
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] It was shown that single adsorbates on metal surfaces with an ultrathin insulator coating can carry a local spin which interacts with the adsorbate surroundings. This interaction leads to a magnetic anisotropy of the local spin, i.e., to the existence of several magnetic energy levels of the adsorbate corresponding to the relative orientation of the local spin with respect to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It was shown that single adsorbates on metal surfaces with an ultrathin insulator coating can carry a local spin which interacts with the adsorbate surroundings. This interaction leads to a magnetic anisotropy of the local spin, i.e., to the existence of several magnetic energy levels of the adsorbate corresponding to the relative orientation of the local spin with respect to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The STM-IETS technique was first applied to the study of vibrational excitations of single molecules on surfaces 1 and has more recently been used to study spin excitations of a single and a few magnetic atoms and molecules deposited on surfaces. [2][3][4][5][6][7][8][9][10][11][12][13] In STM-IETS, electrons tunnel between the tip and the conducting substrate going through the magnetic system. As the bias voltage V is increased, a new conduction channel opens whenever |eV | is larger than the energy of some internal excitation of the atom, which results in a stepwise increase of the differential conductance dI/dV and a peak or dip in the d 2 I/dV 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Low-temperature STM experimental studies revealed that, in certain cases, a local spin could be associated with individual adsorbates at surfaces. Under the variation in the STM bias, the tip-adsorbate junction exhibits conductance steps at well-defined energies in the few meV energy range.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, one can mention several spectacular results obtained in this way: evidence of spin coupling between neighboring atomic adsorbates ͑antiferromagnetic coupling along adsorbed Mn chains͒, 2 large magnetic anisotropy of atomic adsorbates ͑Mn and Fe adsorbates on CuN͒, 3 change in magnetic structure of a molecular adsorbate on various substrates ͑Fe-Phthalocyanine on Cu and CuO͒, 4 evidence of superexchange interactions, 5 interaction of molecular adsorbates with magnetic substrates, 6 and charging of adsorbed magnetic nano-objects. 7 Magnetic transitions could be easily evidenced in these systems due to the presence of a coating on the metal substrate that efficiently decouples the adsorbate from the continua of metallic states. When magnetic atoms are directly adsorbed on a metal, magnetic transitions could be observed but much broadened by the interaction with the substrate.…”
Section: Introductionmentioning
confidence: 99%